Digital Fatigue and Cognitive Load in E‐Learning: Evidence From Nursing Students in Jordan - Shaban Sinnokrot; Randa Khirfan; Ahmad I. Miqdadi; Yousef Abu‐Wardeh; Ala'a Ayman Al‐yyan; Qusai Abdulrahman AbuQamar; Nawras Fashafsheh (Nursing Open, 2026)
ABSTRACT Aim To assess digital fatigue and multidimensional cognitive load, and to examine their associated factors among nursing students engaged in online learning in Jordanian universities. Design A cross‐sectional study. Methods An Internet‐based questionnaire was distributed to undergraduate nursing students from governmental and private universities in Jordan between March and April 2025. Digital fatigue was measured using the Zoom Exhaustion and Fatigue scale, and cognitive load was measured using Leppink's Cognitive Load Scale. Associations were examined using bivariate tests, and a multiple linear regression analysis with bootstrapping was conducted to identify factors independently associated with extrinsic cognitive load. Results A total of 537 nursing students participated. Students reported relatively high levels of digital fatigue and cognitive load, with extrinsic cognitive load showing the pronounced ceiling effect. Digital fatigue was independently associated with extrinsic cognitive load after adjusting for demographic and academic characteristics. Academic year, type of university, and daily digital device use were also independently associated with extrinsic cognitive load, while age, sex, grade point average, device type, and Internet quality showed no significant associations. Conclusion Digital fatigue was independently associated with extrinsic cognitive load among nursing students, highlighting the role of instructional design in shaping students' cognitive experiences. Implications for the Profession and/or Patient Care Nurse educators should prioritise instructional strategies that reduce unnecessary cognitive demands in online learning environments, such as simplified navigation, reduced task‐switching, and structured pacing, to support nursing students' cognitive wellbeing. Impact Digital fatigue and cognitive load remain underexamined among nursing students in resource‐limited settings. This study identifies extrinsic cognitive load as a modifiable, instructional‐design‐related factor, offering nurse educators a concrete target for improving online nursing education. Reporting Method This study adhered to the Strengthening the Reporting of Observational Studies in Epidemiology checklist for cross‐sectional studies. Patient or Public Contribution No patient or public contribution.